Toward simultaneous PET/MR breast imaging: Systematic evaluation and integration of a radiofrequency breast coil. Issue 2 (1st February 2013) - Aklan, Bassim; Paulus, Daniel H.; Wenkel, Evelyn; Braun, Harald; Navalpakkam, Bharath K.; Ziegler, Susanne; Geppert, Christian; Sigmund, Eric E.; Melsaether, Amy; Quick, Harald H.
Abstract : Purpose: : With the recent introduction of integrated whole‐body hybrid positron emission tomography/magnetic resonance (PET/MR) scanners, simultaneous PET/MR breast imaging appears to be a potentially attractive new clinical application. In this study, the technical groundwork toward performing simultaneous PET/MR breast imaging was developed and systematically evaluated in phantom experiments and breast cancer patient hybrid imaging. Methods: : Measurements were performed on a state‐of‐the‐art whole‐body simultaneous PET/MR system (Biograph mMR, Siemens AG, Erlangen, Germany). The PET signal attenuating effects of a MR‐only four‐channel radiofrequency (RF) breast coil that is present in the PET field‐of‐view (FoV) during a simultaneous PET/MR data acquisition has been investigated and quantified. For this purpose, a dedicated PET/MR visible breast phantom featuring four modular inserts with various structures (no insert, MR insert, PET insert, and PET/MR insert) was developed. In addition to a systematic evaluation of MR‐only image quality, the following phantom scans were performed using 18 F radio tracer: (1) PET emission scan with only the homogeneous breast phantom; (2) PET emission scan additionally with the RF breast coil in the PET FoV. Attenuation correction (AC) of PET data was performed with CT‐based three‐dimensional (3D) hardware attenuation maps (μ‐maps) of the RF coil and breast phantom. Finally, a simultaneous PET/MR breast imaging was performed in two breast cancer patients. Results: : The modular breast phantom allowed for systematic evaluation of various MR, PET, and PET/MR image quality parameters. The RF breast coil provided MR images of good image quality, unaffected by PET imaging. The global attenuation of the RF breast coil on the PET emission data was approximately 11%. This hardware attributed PET signal attenuation was successfully corrected by using an appropriate CT‐based 3D μ‐map of the RF breast coil. Imaging of two breast cancer patients confirmed the successful integration of the RF breast coil into the concept of simultaneous PET/MR breast imaging. Conclusions: : The successful integration of a four‐channel RF breast coil with a defined table position together with the CT‐based μ‐maps provides a technical basis for future clinical PET/MR breast imaging applications.